2015
DOI: 10.1177/0284185114562467
|View full text |Cite
|
Sign up to set email alerts
|

128-slice dual-source CT coronary angiography with prospectively electrocardiography-triggered high-pitch spiral mode: radiation dose, image quality, and diagnostic acceptability

Abstract: The radiation dose is lower with HPS than with other modes, and the HPS mode-acquired images of patients with heart rates of ≤65 bpm are nearly acceptable for diagnostic image interpretation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…To buy a new CT scanner is a huge investment for a radiology department and buying a new CT scanner takes often years of budget planning as well as discussions with hospital managers and manufacturers. To date, techniques frequently in use are: automated tube potential selection, iterative reconstruction algorithms, high-pitch CT imaging, and low-kV imaging ( 14 17 ). In particular, low-kV imaging is often used in combination with some of the mentioned other techniques, especially iterative reconstruction algorithms to reduce image noise ( 10 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To buy a new CT scanner is a huge investment for a radiology department and buying a new CT scanner takes often years of budget planning as well as discussions with hospital managers and manufacturers. To date, techniques frequently in use are: automated tube potential selection, iterative reconstruction algorithms, high-pitch CT imaging, and low-kV imaging ( 14 17 ). In particular, low-kV imaging is often used in combination with some of the mentioned other techniques, especially iterative reconstruction algorithms to reduce image noise ( 10 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Montet et al compared a FBP reconstructed protocol with a new iterative reconstruction protocol. The examinations were carried out on a high-end CT scanner system (Discovery 750 HD, GE Healthcare, Milwaukee, WI, USA) (17). The FBP protocol was adjusted to 100 kV, 250 Ref.…”
Section: Discussionmentioning
confidence: 99%
“…For post processing, the obtained data was moved to Syngovia workstation. American Heart Association (AHA) model of 17-segment was used to assess the coronary arteries which includes [-RCA proximal (1); mid (2); distal (3); PDA (4a); PLV (4b); LM (5); LAD proximal (6); mid (7); distal (8); D1 (9); D2 (10); LCX proximal (11); OM1 (12); LCX mid (13); OM2 (14); LCX distal (15); RI (16)]. Stenosis of 50% or more diameter was considered as significant disease of the coronary arteries whereas less than 50% stenosis considered as non-significant disease.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, we can achieve z-direction 48 mm of total coverage in a single rotation. (15,16). As compared to intracardiac catheter examination, Siemens dual source CT scanner dose values are lied far below.…”
Section: Introductionmentioning
confidence: 99%
“…These values are significantly lower than the standard SAS mode [ 30 , 42 , 44 - 47 ]. In all these studies, image quality showed consistently high objective and subjective image quality [ 45 - 47 ], and diagnostic image quality was found in at least 97% of evaluated coronary segments without significant differences to other modes [ 42 , 47 ].…”
Section: Scan Modementioning
confidence: 99%